Pemberdayaan UMKM Desa Linggamekar Melalui Strategi Inovatif Menghadapi Digitalisasi - Sandi Nasrudin Wibowo; Aoliyah Firasati; Adinda Oktaviya; Dwi Salsa Amalia; Delia Noviyanti (Jurnal Pengabdian Tri Bhakti, 2026)
This community service program aimed to empower Micro, Small, and Medium Enterprises (MSMEs) in Linggamekar Village through business legalization, branding development, and digital visibility enhancement. The main issues faced by local MSMEs included lack of business legality, weak brand identity, and limited utilization of digital platforms. The program was implemented through a Thematic Community Service Program (KKN) using a qualitative approach and the Asset-Based Community Development (ABCD) method. Activities included observation, MSME data collection, Business Identification Number (NIB) registration through the Online Single Submission (OSS) system, logo design assistance, and Google Maps registration training. The results showed that 10 MSMEs successfully obtained NIB, developed business logos, and registered their business locations digitally, improving credibility and market visibility. Active participation from business actors indicated increased awareness of digital transformation importance. This initiative demonstrates that structured mentoring can accelerate MSME digital readiness and strengthen local economic resilience.